PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP HUBUNGAN ANTARA MANAJEMEN LABA DENGAN NILAI PERUSAHAAN - Junchristianti, Yessinda; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the influence of profit management to the firm value, the practical of corporate governance to the firm value and the practical influence of corporate governance to the correlation between profit management and the firm value. The result of the research shows that: (1) the earnings management is negative and it does not have any significant influence to the firm value. (2) The practical of corporate governance simultaneously has positive significant influence to the firm value with a difference ways in each variable. The institutional ownership variable, independent commissioner and size of board of commissioner are the variables which have significant influence to the firm value. (3) The institutional ownership, size of board of commissionaires and classification of public accountant are the moderate variables between the earnings management and firm value whereas the managerial ownership, independent commissioner and audit committee is not the moderating variable. Keywords: corporate governance, profit management and firm value